2014
DOI: 10.1016/j.cub.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of Nonsynaptic and Synaptic Plasticity in Operant Reward Learning-Induced Compulsive Behavior

Abstract: These data establish direct causality for the contributions of distinct synaptic and nonsynaptic adaptive processes to complementary facets of a compulsive behavior resulting from operant reward learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 40 publications
7
39
1
Order By: Relevance
“…Second, because many of the key sensory neurons that provide chemoafferent or mechanoafferent inputs to the feeding apparatus have been characterized (Evans et al 2003;Evans and Cropper 1998;Rosen et al 2000aRosen et al , 2000b, working out the cellular mechanism by which sensory feedback can shape motor neuronal activity can focus on both identified sensory and motor neurons. Finally, the studies by Nargeot and his colleagues have elegantly demonstrated that it is possible to work out, at the level of individual identified neurons, the mechanisms by which variability can be reduced in the feeding neural circuitry (Sieling et al 2014), suggesting that similar studies can be done to understand how variability is regulated by sensory feedback. Studies by Benjamin and his colleagues have demonstrated the power of invertebrate systems for exploring the neural mechanisms of behavioral hierarchy (Pirger et al 2014), and the extent to which central pattern generators are hierarchical or distributed systems (Benjamin 2012).…”
Section: Controlling and Exploiting Neuronal And Biomechanical Variabmentioning
confidence: 99%
“…Second, because many of the key sensory neurons that provide chemoafferent or mechanoafferent inputs to the feeding apparatus have been characterized (Evans et al 2003;Evans and Cropper 1998;Rosen et al 2000aRosen et al , 2000b, working out the cellular mechanism by which sensory feedback can shape motor neuronal activity can focus on both identified sensory and motor neurons. Finally, the studies by Nargeot and his colleagues have elegantly demonstrated that it is possible to work out, at the level of individual identified neurons, the mechanisms by which variability can be reduced in the feeding neural circuitry (Sieling et al 2014), suggesting that similar studies can be done to understand how variability is regulated by sensory feedback. Studies by Benjamin and his colleagues have demonstrated the power of invertebrate systems for exploring the neural mechanisms of behavioral hierarchy (Pirger et al 2014), and the extent to which central pattern generators are hierarchical or distributed systems (Benjamin 2012).…”
Section: Controlling and Exploiting Neuronal And Biomechanical Variabmentioning
confidence: 99%
“…Using RTXI, Sieling et al [35] used the dynamic-clamp technique, in which simulated membrane and synaptic currents are artificially added or subtracted from neurons, to examine whether selective changes in single conductances governing cell excitability and electrical coupling are responsible for the associative modification of feeding circuit output and behavior (Fig 6). Using in vitro preparations of buccal ganglia isolated from naive and operantly trained animals, Sieling et al either enhanced or diminished neuronal excitability and coupling strengths in RT to test for causation and determine respective contributions of synaptic and non-synaptic processes by which associative learning leads to expression of compulsive behavior.…”
Section: Resultsmentioning
confidence: 99%
“…In (D), G leak was introduced into a B63 and current pulses for measuring coupling coefficients were injected into either postjunctional B30 or B65. (For details, see [35] Fig. S1.)…”
Section: Resultsmentioning
confidence: 99%
“…16, 2017; cellular/molecular components or forms of plasticity in the process of achieving certain learning goals. This also implies significant animal-to-animal and trial-to-trial variability in the mechanisms that mediate learning, thereby calling for utmost caution in assigning one-to-one relationships between behavioral learning and specific forms of plasticity in any single brain region (Bailey et al, 2006;Bennett and Hacker, 2003;Jazayeri and Afraz, 2017;Krakauer et al, 2017;Mayford et al, 2012;Sieling et al, 2014;Tsokas et al, 2016;Vogelstein et al, 2014).…”
Section: Degeneracy In Learning and Memorymentioning
confidence: 99%
“…http://dx.doi.org/10.1101/203943 doi: bioRxiv preprint first posted online Oct. 16, 2017;Jazayeri and Afraz, 2017;Krakauer et al, 2017;Mayford et al, 2012;Sieling et al, 2014;Tsokas et al, 2016;Vogelstein et al, 2014).…”
Section: The Causality Conundrummentioning
confidence: 99%